The Role of Negative Affect in Emotional Processing of Food-Related Images in Eating Disorders and Obesity - Sierra, Irene; Senín-Calderón, Cristina; Roncero, María; Perpiñá, Conxa (Frontiers in Psychology, 2021)
The aim of the present study was to analyze differences in the emotional processing (valence, arousal, and dominance) of food-related information in patients with eating disorders (ED), patients with obesity, and healthy women. Moreover, the mediator role of negative affect and the moderating role of the diagnostic group (ED vs. non-ED) were analyzed. Method: The sample consisted of 94 women (39 with eating disorders, 19 with obesity, 36 healthy women). Measures: International Affective Picture System (IAPS) food picture exposure task; Self-Assessment Manikin Analogue-Visual Scale (SAM) appraising Arousal, Valence, and Dominance; Eating Attitudes Test (EAT-26); Positive and Negative Affect Schedule (PANAS). Results: Patients with purging symptomatology rated food images as more unpleasant than healthy women. Patients with purging and restrictive eating symptomatology showed higher levels of arousal and less dominance over the emotions experienced. The mediation analysis showed that negative affect mediated the relationship between eating symptomatology (EAT-26) and the Valence of food images, as well as the control over the emotions experienced when viewing food images (Dominance). For the moderation analysis participants were regrouped into two groups (ED patients vs. non-ED patients). The direct relationship between eating symptomatology and food image valence was moderated by the diagnostic group. However, the group did not moderate the direct relationship between the EAT-26 and dominance over experienced emotions, or the indirect effect on eating symptomatology through negative affect. These results show the relevance of negative affect in the emotional processing of food-related information, and they support an eating disorder-disordered eating dimensional perspective.